2018
DOI: 10.5465/amj.2013.1064
|View full text |Cite
|
Sign up to set email alerts
|

When and Why People Engage in Different Forms of Proactive Behavior: Interactive Effects of Self-construals and Work Characteristics

Abstract: LSE has developed LSE Research Online so that users may access research output of the School. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LSE Research Online to facilitate their private study or for non-commercial research. You may not engage in further distribution of the material or use it for any profit-making activities or any commercial gain. You may freely distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 101 publications
4
89
0
Order By: Relevance
“…As discussed above, our review has identified a paucity of research examining how contextual factors influence the direct relationship between individual predictors of team member proactivity and subsequent proactive behavior. We found, for instance, only one recently published article by Wu, Parker, Wu, and Lee (2018) demonstrating that different contextual factors can shape individual or team member proactivity by enabling employees to express their conceptions of individuality. More specifically, their findings show that at the team-level of analysis, individuals with interdependent self-construals (i.e., individuals who see themselves as interdependent with others, Markus & Kitayama, 1991) engage in proactive behaviors, but only when job interdependence is high.…”
Section: Contextual Factors As Moderatorsmentioning
confidence: 84%
“…As discussed above, our review has identified a paucity of research examining how contextual factors influence the direct relationship between individual predictors of team member proactivity and subsequent proactive behavior. We found, for instance, only one recently published article by Wu, Parker, Wu, and Lee (2018) demonstrating that different contextual factors can shape individual or team member proactivity by enabling employees to express their conceptions of individuality. More specifically, their findings show that at the team-level of analysis, individuals with interdependent self-construals (i.e., individuals who see themselves as interdependent with others, Markus & Kitayama, 1991) engage in proactive behaviors, but only when job interdependence is high.…”
Section: Contextual Factors As Moderatorsmentioning
confidence: 84%
“…It also includes behaviours such as contributing to discussions and meetings about the organization's strategy, developing a plan to spend money in one's department and aiding to set goals in one's work area. RBSE has been related to both job performance and job satisfaction in a variety of settings (Luthans et al ., ; Wu, Parker, Wu, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…We used the Situational Judgment Test of Personal Initiative (SJT-PI; Bledow and Frese, 2009) as a measure of proactive behavior (see also Wu et al, 2018). The SJT-PI comprises 12 items, each of which describes a hypothetical but realistic situation that could occur in the workplace.…”
Section: Proactive Behaviormentioning
confidence: 99%